COPD‐dependent effects of genetic variation in key inflammation pathway genes on lung cancer risk. Issue 3 (12th December 2019) - Watza, Donovan; Lusk, Christine M.; Dyson, Gregory; Purrington, Kristen S.; Wenzlaff, Angela S.; Neslund‐Dudas, Christine; Soubani, Ayman O.; Gadgeel, Shirish M.; Schwartz, Ann G.
Abstract : Genome‐wide association studies (GWAS) have identified several loci contributing to lung cancer and COPD risk independently; however, inflammation‐related pathways likely harbor additional lung cancer risk‐associated variants in biologically relevant immune genes that differ dependent on COPD. We selected single nucleotide polymorphisms (SNPs) proximal to 2, 069 genes within 48 immune pathways. We modeled the contribution of these variants to lung cancer risk in a discovery sample of 1, 932 lung cancer cases and controls stratified by COPD status and validation sample of 953 cases and controls also stratified by COPD. There were 43 validated SNPs in those with COPD and 60 SNPs in those without COPD associated with lung cancer risk. Furthermore, 29 of 43 and 28 of 60 SNPs demonstrated a statistically significant interaction with COPD in the pooled sample. These variants demonstrated tissue‐dependent effects on proximal gene expression, enhanced network connectivity and resided together in specific immune pathways. These results reveal that key inflammatory related genes and pathways, not found in prior GWAS, impact lung cancer risk in a COPD‐dependent manner. Genetic variation identified in our study supplements prior lung cancer GWAS and serves as a foundation to further interrogate risk relationships in smoking and COPD populations. Abstract : What's new? Former smokers may have lingering inflammation as a result of smoking, and this inflammation may be the reason that people with COPD have a 2‐ to 3‐fold increased risk of lung cancer. Here the authors looked at a high‐density, multiethnic SNP array to find variants linked to lung cancer risk which occur in genes involved in immune pathways. They found 43 SNPs associated with lung cancer in people with COPD, and 29 of the 43 showed significant biological interaction with COPD. This is the first study to identify SNPs that contribute to lung cancer risk in a COPD‐dependent fashion.